Fifty key Medieval thinkers - Evans, G. R. (Gillian Rosemary) (Routledge key guides., 2002)
Focussing on individuals whose ideas shaped intellectual life between 400 and 1500, Fifty Key Medieval Thinkers is an accessible introduction to those religious, philosophical and political concepts central to the medieval worldview. Including such diverse figures as Bede and Wyclif, each entry presents a biographical outline, a list of works and a summary of their main theories, alongside suggestions for further reading. Chronologically arranged, and with an introductory essay which presents important themes in context, this volume is an invaluable reference tool for all students of.